ANTIMICROBIAL ACTIVITY OF PIPER CAPENSE L.F. EXTRACTS - Thorburn, A.; Cromarty, D.; Steenkamp, V. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Piper capense L.f. (Piperaceae) is a plant used traditionally for the treatment of infectious diseases. It therefore has potential as a source of novel antimicrobial compound/s. In this study antimicrobial activities of P. capense extracts were determined against various pathologically relevant microorganisms using disc diffusion and micro-broth dilution assays. Methanol and acetone extracts of root-bark exhibited MIC values < 1 mg/ml against Staphylococcus aureus (ATCC 12600) and Candida albicans (ATCC 10231). Phytochemical analyses of these extracts using various mobile phases on TLC and selective visualizing reagents revealed the presence of alkaloids, phenols, terpenes and flavonoids. Bioassay-guided fractionation of differentially solubilized or SPE sub-fractions indicated an enhanced antimicrobial activity in a hexane soluble sub-fraction (MIC of 0.02 mg/ml). HPLC analyses using a binary gradient of water (0.1% formic acid) and methanol (0.1% formic acid) revealed four major peaks for the hexane soluble sub-fraction. HPLC eluents were collected in a drop-wise fashion onto silica TLC plates and bioautography indicated that the compound that eluted at 13.6 minutes was responsible for the antimicrobial activity. This compound was further analysed using LC-MS/MS and GC-MS and identified as 5-hydroxy-2-methyl-1,4-naphthoquinone. This is the first time that this compound has been identified in this plant family. 5-hydroxy-2-methyl-1,4-naphthoquinone is reported to have highly toxic properties related to superoxide formation which confirms its antimicrobial activity but also implies non-selective in vivo toxicity. Acknowledgements: NRF and MRC provided funding.